Pentuple Bottom Line in Seaweeds Cultivation: An Environmental Accounting Review - Syamsu ALAM; Roslina ALAM; Eka Ariaty ARFAH (PT Keberlanjutan Strategis Indonesia, 2024)
This study explores the role of environmental and sustainability accounting in promoting sustainable seaweed farming in Indonesia. Environmental accounting records and reports the environmental impacts of economic activities, while sustainability accounting integrates economic, social, and environmental dimensions under the Triple Bottom Line (TBL) and Pentuple Bottom Line (PBL) frameworks. The research highlights how these tools can enhance seaweed farming's global competitiveness, support blue economy development, and address climate change.Using a descriptive qualitative approach, the study combines in-depth interviews with seaweed farmers, academics, and stakeholders with a literature review. Legitimacy theory is applied to analyze how transparency in sustainability reporting strengthens relationships with society and global markets.Findings reveal limited adoption of environmental and sustainability accounting in seaweed farming, despite its potential. Transparency in managing environmental impacts, such as waste and carbon absorption, is critical. Local cultural values like siri’ na pacce serve as a moral foundation for strengthening social legitimacy. Technologies like IoT and blockchain can accelerate effective environmental accounting.This study contributes by integrating environmental and sustainability accounting into the PBL framework, addressing economic, social, and environmental impacts more comprehensively. It emphasizes better governance through farmer awareness, eco-friendly technologies, and stronger regulations, positioning seaweed farming as a blue economy model. Future research should focus on cross-sector collaboration to advance sustainable fisheries and marine policies.